KESANTUNAN BAHASA VERBAL SANTRI KEPADA USTAZ DALAM BERKOMUNIKASI DI MA’HAD TARBIYAH ISLAMIYAH DAR AL-HIKMAH SINGOSARI - M. Ibnu Ma’ruf Effendy; Chalimatus Sa’dijah; Arief Aridiansyah (Vicratina : Jurnal Ilmiah Keagamaan, 2021)
In this study, researchers tried to link moral and moral education with the use of language. There are many declines in moral character in the community that make the government concerned about this situation, thus giving rise to character education; This research can be seen from the research location which is an educational institution in Indonesia that still exists and develops, namely pesantren; The author uses a qualitative approach and case studies with observation and interviews as research methods. To know and analyze the phenomenon; Not all strategies are carried out by students in communicating with the ustaz, there are only three that appear, namely positive politeness, negative politeness, and Bald On Record. However, what Ustadz uses are all types of strategies, namely positive politeness, Bald On Record, negative politeness, and Of Record. Then, in its application the verbal language politeness of the santri and ustaz is applied both when they are in formal or informal situations. The results show that there are no different strategies used in both formal and informal activities. So, neither social distance nor social strength becomes an obstacle to communicating between students and the ustaz.